Digital Wallets and Crypto Payment Systems: A Bibliometric Study of FinTech Integration - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
This study presents a comprehensive bibliometric analysis of the academic literature surrounding digital wallets and crypto payment systems, two pivotal components of the evolving FinTech landscape. By utilizing data from the Scopus database and visualizing it through VOSviewer, the study maps co-occurrence of keywords, co-authorship networks, institutional collaboration, and country-level partnerships. Findings reveal that blockchain technology serves as the central anchor of research, connecting diverse themes such as smart contracts, authentication, digital assets, and decentralized finance (DeFi). Temporal analyses show a progression from foundational infrastructure studies to more application-driven topics like non-fungible tokens (NFTs) and crypto wallets. Co-authorship and collaboration networks highlight key contributors and regions, with India, the United States, and select European countries leading scholarly production and partnerships. The study provides theoretical contributions by identifying core research clusters and emerging themes, while offering practical implications for regulators, developers, and financial service providers aiming to integrate digital and crypto payment solutions. Limitations include database scope and the inherent constraints of bibliometric methods, suggesting avenues for future mixed-method or qualitative enrichment.